The Digital Maturity as a predictor of Organizational Resilience during a Severe Crisis - Rotem, Dorit; Fisher, Eddie (Business and Economic Research, 2022)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The COVID-19 pandemic spread around the world in early 2020, forcing governments to impose lockdowns. As a result, organizations had to find new ways to continue operating during this disruptive event. Not all organizations were able to use digital technology with the same degree of success. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">This mainly qualitative study includes the use of mixed methods aimed to investigate the significance of digital maturity for an organization, so that it can develop resilience during a pandemic and retain competitiveness in a post-pandemic age, referred to as ‘the new normal’. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">The outcome of this research suggests that under certain assumptions the digital maturity of an organization was a good predictor of its organizational resilience during the pandemic. The most influential factors in successfully coping with such event included both technical and managerial activities such as the existence of an adequate technological infrastructure, agile decision making, monitoring the situation, and improving the digital literacy of the workforce. This study also identified the practices that are likely to be adopted in the post-pandemic era. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">These outcomes were incorporated into a new model for managing disruptive events using digital technology ready for adoption by any kind of business, provided that geographical and cultural differences are considered and appropriate modifications are applied.